Penetapan Kadar Total Flavonoid Ekstrak Kulit Buah Limpasu (Baccaurea lanceolata) dengan Metode Spektrofotometri Uv-Vis - Risa Ahdyani (JURNAL FARMASI DAN MAKANAN, 2022)
Limpasu (Baccaurea lanceolata) is a native plant of Borneo which is used empirically to protect the skin from sun exposure. Limpasu contains flavonoid compounds which generally act as antioxidants. This study aims to determine the total flavonoid content of limpasu pericarp extract by using UV-Vis spectrophotometry method. Limpasu pericarp was extracted by using the stratification maceration method. This extraction was carried out by immersing the simplicia into three types of solvents with different polarities, respectively, namely n-hexane (nonpolar), ethyl acetate (semi-polar), and methanol (polar). The concentration of n-hexane, ethyl acetate, and methanol extracts was determined using a UV-Vis spectrophotometer at a maximum wavelength of 510 nm with quercetin as standard. Based on the test, it was found that the total flavonoid content of pericarp extracts, hexane, ethyl acetate, and methanol, respectively, was 44.1552 g/ml; 155.8506 g/ml; and 25.8506 g/ml. The highest total flavonoid content was found in the ethyl acetate extract.